The influence of work environment and competence on employee performance is mediated by work motivation at the Secretariat Office of the DPRD of Bombana Regency, Southeast Sulawesi. Master of Management Study Program Stie Enam Enam Kendari - Jusriadi, Andi; Nur, Muh.; Yuana, Indira (Riviera Publishing, 2025)
This study aims to determine and analyze the Influence of Work Environment on Work Motivation at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. The Influence of Competence on Work Motivation at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. The Influence of Work Motivation on Employee Performance at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. The Influence of Work Environment on Employee Performance at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. The Influence of Competence on Employee Performance at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. The Role of Work Motivation in Mediating the Influence of Work Environment on Employee Performance at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. The Role of Work Motivation in Mediating the Influence of Competence on Employee Performance at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. The population in this study were 33 employees of the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara, so that 33 employees of the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara were used as samples. The results of this study indicate that the work environment has a positive and significant effect on work motivation at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. Competence has a positive and significant effect on work motivation at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. Work motivation has a positive and significant effect on employee performance at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. The work environment has a positive and significant effect on employee performance at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. Competence has a positive and significant effect on employee performance at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. Work motivation does not play a role in mediating the influence of the work environment on employee performance at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara. Work motivation plays a role in mediating the influence of competence on employee performance at the Kantor Sekretariat DPRD Kabupaten Bombana Sulawesi Tenggara.